2014
DOI: 10.1021/ct500830a
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Franck–Condon Methods for Computing Vibrationally Broadened UV–vis Absorption Spectra of Flavin Derivatives: Riboflavin, Roseoflavin, and 5-Thioflavin

Abstract: We address the performance of the vertical and adiabatic Franck–Condon (VFC/AFC) approaches combined with time-independent or time-dependent (TI/TD) formalisms in simulating the one-photon absorption spectra of three flavin compounds with distinct structural features. Calculations were done in the gas phase and in two solvents (water, benzene) for which experimental reference measurements are available. We utilized the independent mode displaced harmonic oscillator model without or with frequency alteration (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 104 publications
5
48
0
Order By: Relevance
“…In the observed FT-IR spectrum of NF-DMAP salt, the N23-H24 stretch is seen at 3134 cm −1 , whereas it is calculated as 3458 and 3263 cm −1 , using wB97X-D and B3LYP level of theory, respectively. The peak of free N-H bond falls in the range 3600-3400 cm −1 [39][40][41]. However, the N-H peak in NF-DMAP is somewhat lower than this range.…”
Section: Vibrational Wavenumbers Involved In Hydrogen Bondingmentioning
confidence: 89%
See 1 more Smart Citation
“…In the observed FT-IR spectrum of NF-DMAP salt, the N23-H24 stretch is seen at 3134 cm −1 , whereas it is calculated as 3458 and 3263 cm −1 , using wB97X-D and B3LYP level of theory, respectively. The peak of free N-H bond falls in the range 3600-3400 cm −1 [39][40][41]. However, the N-H peak in NF-DMAP is somewhat lower than this range.…”
Section: Vibrational Wavenumbers Involved In Hydrogen Bondingmentioning
confidence: 89%
“…As the comparison is made between the calculated (gaseous phase) and experimental (solid state) spectra and the anharmonicity effects are also not included, the calculated wave numbers found in the present study are somewhat greater than the observed ones. Consequently, the computed wavenumbers are reduced by 0.980 and 0.991 for wB97X-D and B3LYP functionals, respectively, to eliminate anharmonicity existing in real system [39][40][41]. The main motive to discuss the vibrational modes corresponding to the bands affected by hydrogen bonds in the salt is to give information related to the functional groups, i.e., whether they are bonded or non-bonded, and to confirm the transfer of proton from NF − to DMAP + and also to know the sites which took part in forming hydrogen bond between NF (API) and DMAP (coformer), which are responsible for making NF-DMAP salt.…”
Section: Vibrational Assignmentmentioning
confidence: 99%
“…For comparison to Table 2 , the TD-CAM-B3LYP vertical excitation energies for the bright state of the Anderson/Jung structures are 371/374 nm (regardless of dispersion correction), resulting in a small red shift of 0.03 eV. Given the nature and the physical meaning of vertical excitation energies (namely an upper limit to the range in which the photophysics take place, Götze and Thiel, 2013 ; Karasulu et al, 2014 ), the apparent “overestimation” resulting from the CAM-B3LYP calculations is indeed more realistic than the reproduction of a measured absorption maximum. While it is experimentally established that the electron transfer from Tyr21 to FMN leads to the formation of the red-shifted species, it has so far not been considered that the resulting change in local dipole moment might already strongly perturb the hydrogen bond network around the flavin.…”
Section: A Photocycle For the Trp-in Resting Statementioning
confidence: 98%
“…Vibrational broadening can be also included via the vertical and adiabatic Franck-Condon approaches (VFC and AFC) as demonstrated by Karasulu et al for flavin derivatives (83). However, since the gas-phase experiment on lumiflavin has not been done yet, the reproduction of the bandshapes of UV spectra is out-of-scope of the current study.…”
Section: Solvatochromic Effects On Vertical Excitation Energiesmentioning
confidence: 99%